Microwave-Assisted Synthesis for Environmentally ZnO Nanoparticle Synthesis - Norlin, Pauzi; Norashikin, Mat Zain; Nurul Amira, Ahmad Yusof (Springer Singapore, 2019)
Zinc oxide (ZnO) nanoparticles are versatile materials in many applications due to their unique chemical and physical properties. Recently, researchers tend to find the fast, simple, cost effective and eco-friendly method to synthesis ZnO nanoparticles. Microwave heating method has special heating capabilities have produced desirable products of ZnO nanoparticles. In this study, ZnO nanoparticles were synthesized by a precipitating method assisted with microwave heating method. Zinc nitrate had been used as zinc salt, sodium hydroxide as reducing agent and gum arabic as stabilizing agent. The objective of this paper was to determine the optimum microwave heating power to obtain small size of ZnO nanoparticles. The powers for microwave heating were selected at 250–850 W with 4 min synthesis time. All the synthesized microwave conditions gave single phase of ZnO with wurtzite structure. Dynamic Light Scattering (DLS) was employed to measure the size of ZnO nanoparticles. The size of ZnO nanoparticles increased with increasing microwave power from 250–850 W. At 350 W, smaller size of ZnO nanoparticles obtained. The Ultraviolet–visible spectroscopy (UV–vis) absorption spectra were found in the range of 340 nm. The Fourier-transform infrared spectroscopy (FTIR) spectra showed peaks range from 424 to 475 cm−1 which indicating standard of Zn–O stretching.